Debt procedure in Islamic perspective and practice research among students in College Angsana / Mohamad Sadiq Umair Nahar. - Nahar, Mohamad Sadiq Umair (2019)
Debt is a part of muamalah that allows by Islam. Debt also can bring a person to heaven if the does so in accordance with the prescribed guidelines or otherwise if a person do what is forbidden by Allah. There are many problems related to debt that happen today especially in relation to usury and manners between debtors and lenders even with close friend. So, debt must be managed wisely and follow the guidelines that have been stated in Quran and Sunnah to avoid from what is forbidden by Allah and do things that can make us closer to Allah. Therefore, in this research will discuss on the debt concept according to Islamic perspective by means of us to look back whether debt is a necessity or not and its practice among students. The research was conducted using a library research and survey method by distribute questionnaire in order to achieve research objectives. Data collected from students in college Angsana, UiTM Puncak Alam. This research is important in order to know how students manage their debt and its practice. The outcome of this research has found out that mostly of the students practice the debt procedure accordance to Islamic perspective.